Effectiveness of Cyclic Sighing on Respiratory Rate and Function in Patients with Pneumonia - Hasaini, Asni; Muhlisoh, Muhlisoh; Sukmawaty, Martini Nur (Indonesian Journal of Global Health Research, 2024)
Pneumonia is a major cause of morbidity and mortality worldwide, occurring not only in those aged >65 years but also in adults with comorbid conditions. The prognostic factor of pneumonia is closely related to respiratory frequency so it is included in standardized prognostic tools. Cyclic sighing (CS) is a method of sighing that affects the dynamics of respiratory control. Objective : to analyze the effectiveness of cyclic sighing on respiratory frequency and pulmonary function in patients with pneumonia at RSD Idaman Banjarbaru. Method : research design Pretest-Posttest Control Group Design. The sample of this study was 20 respondents with purposive sampling divided into 2 groups, the first group was the intervention group which was given cyclic sighing treatment for 6 consecutive days with the implementation of 5 times per day for 5 minutes and the second group was the control group which received therapy according to the hospital with purposive sampling. The research instrument was an observation sheet. Bivariate data analysis using wilcoxon and mann withney tests. Result : There was a significant difference in the intervention group with the control after being given cyclic sighing on the frequency of breathing with an effectiveness value of 98.6%, but there was no difference in the intervention group with the control after being given cyclic sighing on lung function. Conclusions : It is recommended that the intervention of giving cyclic sighing can be used as one of the nursing interventions with pnemonia as a management action for complaints of tightness.